Composite material, film and luminescent device
By setting a second shell with a small band gap width in the quantum dot structure of the quantum dot light emitting device, the problem of the core-shell structure hindering hole injection is solved, and charge balance and high luminous efficiency are achieved.
Patent Information
- Application Number
- CN202311331158.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-13
- Publication Date
- 2025-04-15
AI Technical Summary
The core-shell structure of the existing quantum dot structure hinders the injection of holes, resulting in charge imbalance in the QLED light emitting device.
A composite material is used, and its inner core covers the first shell layer, the second shell layer and the third shell layer from the inside to the outside. By providing a second shell layer with a small band gap width between the first shell layer and the third shell layer, the barrier to hole injection is reduced and hole injection is promoted.
The charge balance in the QLED light emitting device is achieved, non-radiative recombination such as Auger recombination is reduced, the luminescence efficiency of quantum dots is improved, and the high photoluminescence quantum efficiency is maintained.
Smart Images

Figure CN119823747A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of display technology, and more specifically, to a composite material, a thin film, and a light-emitting device. Background Technology
[0002] Quantum dot light-emitting diodes (QLEDs) have the advantages of saturated emitted light color and tunable wavelength, and have a high photoluminescence quantum yield, making them a strong competitor to organic light-emitting diodes (OLEDs) in recent years.
[0003] The quantum dot structure in the quantum dot light-emitting layer of the commonly used QLED structure usually adopts a core-shell structure. The band gap of the shell layer of the core-shell structure gradually widens in the radial direction from the core to the outer shell. The outermost shell layer has the widest band gap, which hinders the injection of charge carriers, especially holes, resulting in charge imbalance in the QLED light-emitting device. Summary of the Invention
[0004] The technical problem to be solved by the embodiments of this application is that the core-shell structure of the existing quantum dot structure hinders the injection of holes, resulting in charge imbalance in the QLED light-emitting device.
[0005] To address the aforementioned technical problems, this application provides a composite material, employing the technical solution described below:
[0006] A composite material includes a core and a first shell, a second shell, and a third shell that are sequentially covered outward from the core;
[0007] The band gap width of the first shell is greater than that of the second shell, and the band gap width of the third shell is greater than that of the second shell.
[0008] Furthermore, the first shell layer comprises at least two layers, and the band gap of the first shell layer gradually increases radially from the core to the third shell layer;
[0009] And / or, the third shell comprises at least two layers, wherein the band gap of the third shell gradually increases radially from the core to the third shell.
[0010] Furthermore, the conduction band of the third shell is higher than that of the first shell, and the conduction band of the first shell is higher than that of the second shell;
[0011] The valence band of the third shell is lower than that of the first shell, and the valence band of the first shell is lower than that of the second shell.
[0012] Furthermore, the band gap width of the first shell layer is 2–3 eV; and / or,
[0013] The band gap width of the second shell is less than 2 eV; and / or,
[0014] The band gap width of the third shell is greater than 3 eV; and / or,
[0015] The bandgap width of the core is 1.5 to 2 eV.
[0016] Furthermore, the core material is selected from at least one of group II-VI compounds, group III-V compounds, group II-V compounds, group III-VI compounds, group IV-VI compounds, group I-III-VI compounds, group II-IV-VI compounds, or group IV elements, wherein the core material is selected from at least one of CdSe, CdS, ZnSe, ZnS, CdTe, CdZnS, CdZnSe, ZnSeS, ZnSeTe, ZnTeS, CdSeS, CdSeTe, CdTeS, CdZnSeS, CdZnSeTe, CdZnSTe, CdSeSTe, ZnSeSTe, CdZnSeSTe, InP, InAs, InAsP; and / or,
[0017] The materials of the first shell, the second shell, and the third shell are selected from at least one of CdS, ZnSe, ZnS, CdSeS, and ZnSeS.
[0018] Furthermore, the composite material is at least one of CdSe@CdS@CdSe@ZnS, CdSe@CdSeS@CdSe@ZnS, CdSeS@CdS@CdSe@ZnS, CdSeS@CdZnS@CdS@ZnS, and CdSeS / CdZnS / CdSeS / ZnS.
[0019] Furthermore, the thickness of the core is 1–10 nm; and / or,
[0020] The thickness of the first shell layer is 1–10 nm; and / or,
[0021] The thickness of the second shell is 1–10 nm; and / or,
[0022] The thickness of the third shell is 1–10 nm.
[0023] Furthermore, the composite material also includes an organic ligand, and the surface of the third shell layer is connected to the organic ligand.
[0024] Furthermore, the organic ligand is selected from at least one of acid ligands, thiol ligands, amine ligands, (oxy)phosphine ligands, phospholipids, lecithin, polyvinylpyridine, etc., wherein the acid ligand includes at least one of decaenoic acid, undecenoic acid, tetradecanoic acid, oleic acid, and stearic acid; the thiol ligand includes at least one of octaalkylthiol, dodecylthiol, and octadecylthiol; the amine ligand includes one or more of oleylamine, octadecylamine, and octadecylamine; and the (oxy)phosphine ligand includes at least one of trioctylphosphine and trioctylphosphine oxide.
[0025] This application also provides a thin film, which adopts the technical solution described below:
[0026] A thin film, the material of which comprises a composite material as described above.
[0027] This application also provides a light-emitting device, which adopts the technical solution described below:
[0028] A light-emitting device includes an anode layer, a hole-functional layer, a light-emitting layer, an electron-functional layer, and a cathode layer stacked sequentially.
[0029] The light-emitting layer is a thin film as described above.
[0030] Furthermore, the materials of the anode layer and / or the cathode layer include one or more of metals, carbon materials, and metal oxides. The metals include one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb, and Mg; the carbon materials include one or more of graphite, carbon nanotubes, graphene, and carbon fibers; the metal oxides include doped or undoped metal oxides, including one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO, and AMO, or composite electrodes consisting of metal sandwiched between doped or undoped transparent metal oxides. These composite electrodes include one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2, and TiO2 / Al / TiO2; and / or...
[0031] The hole functional layer includes a hole injection layer and a hole transport layer. The materials of the hole injection layer and / or the hole transport layer include at least one of TFB, CuPc, PVK, Poly-TPD, PFB, DNTPD, TCATA, TCCA, CBP, TPD, NPB, NPD, PEDOT:PSS, TAPC, MCC, F4-TCNQ, HATCN, 4,4',4'-tris(N-3-methylphenyl-N-phenylamino)triphenylamine, polyaniline, transition metal oxides, transition metal sulfides, transition metal tin compounds, doped graphene, undoped graphene, and C60; and / or,
[0032] The electronic functional layer includes an electron transport layer, the material of which includes inorganic and / or organic materials. The inorganic material is selected from at least one of the following: doped or undoped zinc oxide, barium oxide, aluminum oxide, nickel oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, nickel oxide, lithium titanium oxide, zinc aluminum oxide, zinc manganese oxide, zinc tin oxide, lithium zinc oxide, indium tin oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc tin sulfide, indium phosphide, gallium phosphide, copper indium sulfide, copper gallium sulfide, and barium titanate. The doped element includes at least one of aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium. The organic material is selected from at least one of quinoxaline compounds, imidazole compounds, triazine compounds, fluorene-containing compounds, and hydroxyquinoline compounds.
[0033] Compared with the prior art, the embodiments of this application have the following main advantages:
[0034] The composite material provided in this application incorporates a second shell with a small bandgap between the first and third shells. This allows holes to tunnel through the third shell into the composite material, while the second shell lowers the potential barrier for hole injection, acting as a springboard to facilitate hole injection. This promotes hole injection without affecting electron injection, resulting in a balance between the number of holes and electrons in the core, achieving charge balance, reducing non-radiative recombination such as Auger recombination, and improving the luminescence efficiency of quantum dots. Furthermore, the first shell restricts the excitons formed by the combination of holes and electrons, thereby maintaining the composite material's high photoluminescence quantum efficiency. Attached Figure Description
[0035] To more clearly illustrate the solution of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0036] Figure 1This is a schematic diagram of the structure of the composite material according to an embodiment of this application;
[0037] Figure 2 This is a schematic diagram of the energy levels of the composite material in an embodiment of this application.
[0038] Figure label:
[0039] 1. Kernel; 2. First shell; 3. Second shell; 4. Third shell. Detailed Implementation
[0040] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs; the terminology used herein in the specification of the application is for the purpose of describing particular embodiments only and is not intended to be limiting of the application; the terms "comprising" and "having," and any variations thereof, in the specification, claims, and foregoing drawings of this application are intended to cover non-exclusive inclusion. The terms "first," "second," etc., in the specification, claims, or foregoing drawings of this application are used to distinguish different objects, not to describe a particular order.
[0041] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0042] Examples of composite materials in this application
[0043] Please see Figure 1 , Figure 2 As shown, an embodiment of this application provides a composite material comprising: a core 1 and a first shell layer 2, a second shell layer 3, and a third shell layer 4 sequentially covering the core 1 outwards.
[0044] The band gap width of the first shell 2 is greater than that of the second shell 3, and the band gap width of the third shell 4 is greater than that of the second shell 3. The composite material provided in this application, by setting a second shell 3 with a small band gap width between the first shell 2 and the third shell 4, allows holes to tunnel through the third shell 4 into the composite material. The second shell 3 lowers the potential barrier for hole injection, acting as a springboard to facilitate hole injection, thereby promoting hole injection without affecting electron injection. This balances the number of holes and electrons in the core 1, achieving charge balance, reducing non-radiative recombination such as Auger recombination, and improving the luminescence efficiency of the quantum dot. Furthermore, the first shell 2 restricts the excitons formed by the combination of holes and electrons, thus maintaining the composite material's high photoluminescence quantum efficiency.
[0045] In some embodiments, the first shell layer 2 includes at least two layers, and the band gap of the first shell layer 2 gradually increases in the radial direction from the core 1 to the third shell layer 4. For example, the first shell layer 2 includes a first sub-shell layer and a second sub-shell layer, the first sub-shell layer covers the core 1, the second sub-shell layer covers the first sub-shell layer, and the second shell layer 3 covers the second sub-shell layer. The band gap of the first sub-shell layer is greater than the band gap of the core 1, the band gap of the second sub-shell layer is greater than the band gap of the first sub-shell layer, and the band gap of the second sub-shell layer is greater than the band gap of the second shell layer 3.
[0046] This application improves the structural stability of the composite material by setting multiple shells in the first shell 2. In addition, the gradually increasing band gap from the inside to the outside of the multiple first shells 2 is conducive to the input of charge carriers. Since the effective mass of holes is greater than that of electrons, the setting of multiple first shells 2 can improve the hole injection efficiency, thereby reducing non-radiative recombination such as Auger recombination and improving the luminescence efficiency of quantum dots.
[0047] In some embodiments, the third shell layer 4 comprises at least two layers, and the band gap of the third shell layer 4 gradually increases in the radial direction from the core 1 to the third shell layer 4. For example, the third shell layer 4 comprises a third sub-shell layer and a fourth sub-shell layer, the third sub-shell layer covering the second shell layer 3, and the fourth sub-shell layer covering the third sub-shell layer. The band gap of the third sub-shell layer is larger than that of the second shell layer 3, the band gap of the fourth sub-shell layer is larger than that of the third shell layer, and the band gap of the third sub-shell layer is larger than that of the second shell layer. In this embodiment, an organic ligand is attached to the outer surface of the fourth sub-shell layer.
[0048] This application improves the structural stability of the composite material by setting up a multi-layered third shell 4. In addition, the gradually increasing band gap of the multi-layered third shell 4 from the inside to the outside is beneficial to the input of charge carriers. Since the effective mass of holes is greater than that of electrons, the multi-layered third shell 4 can improve the hole injection efficiency and increase the number of holes injected into the second shell 3, thereby increasing the number of holes injected into the core 1, improving the charge balance of the core 1, reducing non-radiative recombination such as Auger recombination, and improving the luminescence efficiency of the quantum dot. Furthermore, by setting the band gap of the innermost third shell 4 to be greater than that of the outermost first shell 2, it is possible to further prevent excitons from being output outside the quantum dot and maintain the composite material with a high photoluminescence quantum efficiency.
[0049] Please see Figure 2 As shown, in this embodiment, the conduction band of the third shell 4 is higher than that of the first shell 2, and the conduction band of the first shell 2 is higher than that of the second shell 3; the valence band of the third shell 4 is lower than that of the first shell 2, and the valence band of the first shell 2 is lower than that of the second shell 3. By using the springboard effect of the second shell 3, the number of holes injected into the core 1 through the first shell 2 can be increased, thereby improving the charge balance of the core 1, reducing non-radiative recombination such as Auger recombination, and improving the luminescence efficiency of the quantum dot.
[0050] In some embodiments, the bandgap of the core 1 may be the same as or different from the bandgap of the second shell 3, and both the bandgap of the core 1 and the bandgap of the second shell 3 are smaller than the gap of the first shell 2. In this embodiment, the bandgap of the core 1 and the bandgap of the second shell 3 are the same, that is, the valence band of the core 1 and the valence band of the second shell 3 are the same, such as... Figure 2 As shown, since the band gap of the core 1 is smaller than that of the first shell 2, the valence band of the core 1 is always higher than that of the first shell 2, thereby ensuring that electron-hole pairs recombine in the core 1 while reducing non-radiative recombination such as Auger recombination and improving the luminescence efficiency of the quantum dot.
[0051] In other embodiments, the band gap of the kernel 1 may be smaller than the band gap of the second shell 3, that is, the valence band of the kernel 1 is higher than the valence band of the second shell 3; or, the band gap of the kernel 1 may be larger than the band gap of the second shell 3, that is, the valence band of the kernel 1 is lower than the valence band of the second shell 3.
[0052] In some embodiments, the material of the core 1 is selected from at least one of group II-VI compounds, group III-V compounds, group II-V compounds, group III-VI compounds, group IV-VI compounds, group I-III-VI compounds, group II-IV-VI compounds, or group IV elements, wherein the material of the core is selected from at least one of CdSe, CdS, ZnSe, ZnS, CdTe, CdZnS, CdZnSe, ZnSeS, ZnSeTe, ZnTeS, CdSeS, CdSeTe, CdTeS, CdZnSeS, CdZnSeTe, CdZnSTe, CdSeSTe, ZnSeSTe, CdZnSeSTe, InP, InAs, and InAsP.
[0053] The materials of the first shell 2, the second shell 3 and the third shell 4 are selected from at least one of CdS, ZnSe, ZnS, CdSeS and ZnSeS.
[0054] In some embodiments, the band gap width of the first shell layer 2 is 2 to 3 eV, the band gap width of the second shell layer 3 is less than 2 eV, the band gap width of the third shell layer 4 is greater than 3 eV, and the band gap width of the core 1 is preferably 1.5 to 2 eV. The band gap width of the second shell layer 3 is preferably 1.5 to 2 eV, and the band gap width of the core 1 is equal to or different from the band gap width of the second shell layer 3.
[0055] In this embodiment, the core 1 of the composite material is made of cadmium selenide (CdSe), the first shell 2 is made of cadmium sulfide (CdS), the second shell 3 is made of cadmium selenide (CdSe), and the third shell 4 is made of zinc sulfide (ZnS). The band gap of CdSe is 1.7 eV, the band gap of CdS is 2.42 eV, and the band gap of ZnS is 3.7 eV. This satisfies the following conditions: the band gap of the core 1 is the same as the band gap of the second shell 3; the band gap of the first shell 2 is greater than the band gap of the core 1; the band gap of the first shell 2 is greater than the band gap of the second shell 3; and the band gap of the third shell 4 is greater than the band gap of the first shell 2. The composite material is CdSe@CdS@CdSe@ZnS, where @ represents encapsulation, and A@B indicates that B encapsulates A. The composite material includes a core of CdSe and first shells CdS, second shells CdSe, and third shells ZnS, which are sequentially encapsulated from the inside out.
[0056] In other embodiments, the structure of the composite material may also be at least one of CdSe@CdSeS@CdSe@ZnS, CdSeS@CdS@CdSe@ZnS, CdSeS@CdZnS@CdS@ZnS, CdSeS / CdZnS / CdSeS / ZnS, wherein @ represents encapsulation, and A@B indicates that B encapsulates A.
[0057] In some embodiments, the thickness of the core 1 is 1 to 10 nm, for example: 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm.
[0058] The thickness of the first shell layer 2 is 1 to 10 nm, for example: 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm.
[0059] The thickness of the second shell layer 3 is 1 to 10 nm, for example: 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm.
[0060] The thickness of the third shell layer 4 is 1 to 10 nm, for example: 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm.
[0061] By setting the thickness as described above, the structural strength of the composite material and the hole injection efficiency can be improved. If the thickness of each layer of the composite material is too thin, the structural strength of the composite material will be insufficient; if the thickness of each layer of the composite material is too thick, it will affect the hole injection efficiency, reduce the number of hole injection nuclei, thereby causing charge imbalance of quantum dots, and thus affecting the luminous efficiency of optical devices.
[0062] In this embodiment, the composite material further includes an organic ligand (not shown in the figure), and the surface of the third shell layer 4 is connected to the organic ligand.
[0063] The organic ligand is selected from at least one of acid ligands, thiol ligands, amine ligands, (oxy)phosphine ligands, phospholipids, lecithin, polyvinylpyridine, etc., wherein the acid ligand includes at least one of decaic acid, undecenoic acid, tetradecanoic acid, oleic acid and stearic acid; the thiol ligand includes at least one of octaalkylthiol, dodecylthiol and octadecylthiol; the amine ligand includes one or more of oleylamine, octadecylamine and octadecylamine; and the (oxy)phosphine ligand includes at least one of trioctylphosphine and trioctylphosphine oxide.
[0064] Examples of the films of this application
[0065] This application also provides a thin film, the material of which includes the composite material described above.
[0066] The thin film provided in this application embodiment is prepared using the above-mentioned composite material, which can increase the number of injected charge carriers and promote charge balance within the thin film, thereby improving the photoluminescence efficiency of the thin film.
[0067] Embodiments of the light-emitting devices of this application
[0068] This application provides a light-emitting device, comprising an anode layer, a hole-functional layer, a light-emitting layer, an electron-functional layer, and a cathode layer stacked sequentially.
[0069] The light-emitting layer is a thin film as described above.
[0070] In this embodiment, the light-emitting device has an upright structure and includes an anode layer, a hole-functional layer, a light-emitting layer, an electron transport layer, and a cathode layer stacked sequentially from bottom to top.
[0071] The hole functional layer includes a stacked hole injection layer and a hole transport layer. The material of the hole functional layer includes at least one of TFB, CuPc, PVK, Poly-TPD, PFB, DNTPD, TCATA, TCCA, CBP, TPD, NPB, NPD, PEDOT:PSS, TAPC, MCC, F4-TCNQ, HATCN, 4,4',4'-tris(N-3-methylphenyl-N-phenylamino)triphenylamine, polyaniline, transition metal oxides, transition metal sulfides, transition metal tin compounds, doped graphene, undoped graphene, and C60.
[0072] The luminescent layer is made of a composite material comprising a core, a first shell, a second shell, a third shell, and an organic ligand. The first shell covers the core, the second shell covers the first shell, and the third shell covers the second shell. The band gap of the first shell is larger than that of the core, the band gap width of the first shell is larger than that of the second shell, and the band gap width of the third shell is larger than that of the second shell. The core material is selected from at least one of group II-VI compounds, group III-V compounds, group II-V compounds, group III-VI compounds, group IV-VI compounds, group I-III-VI compounds, group II-IV-VI compounds, or group IV elements. The core material is selected from CdSe, CdS, ZnSe, ZnS, CdTe, CdZnS, CdZnSe, ZnSeS, ZnSeTe, ZnTeS, and CdS. At least one of eS, CdSeTe, CdTeS, CdZnSeS, CdZnSeTe, CdZnSTe, CdSeSTe, ZnSeSTe, CdZnSeSTe, InP, InAs, and InAsP; the materials of the first shell, the second shell, and the third shell are selected from at least one of CdS, ZnSe, ZnS, CdSeS, and ZnSeS; the materials of the organic ligands are selected from at least one of acid ligands, thiol ligands, amine ligands, (oxy)phosphine ligands, phospholipids, lecithin, polyvinylpyridine, etc., wherein the acid ligands include at least one of decaic acid, undecenoic acid, tetradecanoic acid, oleic acid, and stearic acid; the thiol ligands include at least one of octaalkylthiol, dodecylthiol, and octadecylthiol; the amine ligands include one or more of oleylamine, octadecylamine, and octadecylamine; and the (oxy)phosphine ligands include at least one of trioctylphosphine and trioctylphosphine oxide.
[0073] The electron transport layer is made of inorganic and / or organic materials; the inorganic materials are selected from one or more of the following: doped or undoped zinc oxide, barium oxide, aluminum oxide, nickel oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, nickel oxide, lithium titanium oxide, zinc aluminum oxide, zinc manganese oxide, zinc tin oxide, zinc lithium oxide, indium tin oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc tin sulfide, indium phosphide, gallium phosphide, copper indium sulfide, copper gallium sulfide, and barium titanate; the doped elements include one or more of aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium; the organic materials are selected from one or more of the following: quinoxaline compounds, imidazole compounds, triazine compounds, fluorene-containing compounds, and hydroxyquinoline compounds.
[0074] The materials of the anode layer and / or cathode layer include one or more of metals, carbon materials, and metal oxides. The metals include one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb, and Mg. The carbon materials include one or more of graphite, carbon nanotubes, graphene, and carbon fibers. The metal oxides include doped or undoped metal oxides, including one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO, and AMO, or composite electrodes consisting of metal sandwiched between doped or undoped transparent metal oxides. The composite electrodes include one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2, and TiO2 / Al / TiO2.
[0075] The light-emitting device provided in this application includes a light-emitting layer made of the composite material. The composite material includes a second shell layer located between the first shell layer and the third shell layer. The band gap of the first shell layer is larger than that of the second shell layer, and the band gap of the third shell layer is larger than that of the second shell layer. This configuration promotes hole injection without affecting electron injection, balancing the number of charge carriers in the composite material. This achieves charge balance in the quantum dots, reducing non-radiative recombination such as Auger recombination and improving the luminous efficiency of the quantum dots, thereby improving the luminous efficiency of the light-emitting device. Furthermore, by setting the band gap of the first shell layer to be larger than that of the core, after the equally distributed number of holes and electrons in the injected core combine to form excitons, the wide band gap of the first shell layer confines the excitons, restricting their output from the core, thus maintaining a high photoluminescence quantum efficiency of the light-emitting device.
[0076] The above solution will be further described below with reference to specific embodiments. The preferred embodiments of the present invention are described in detail below:
[0077] Example 1:
[0078] (1) Provide a glass substrate and place the glass substrate inside a nitrogen glove box.
[0079] (2) An ITO anode is prepared on the glass substrate.
[0080] (3) The water-soluble conductive polymer PEDOT:PSS is spin-coated onto the ITO anode, dried to form a film, and then annealed at an ambient temperature of 150°C for 15 min to form a hole injection layer, wherein the thickness of the hole injection layer is 45 nm.
[0081] (4) TFB ink is spin-coated onto the hole injection layer, dried to form a film, and then annealed at an ambient temperature of 230°C for 30 minutes to form a hole transport layer, wherein the thickness of the hole transport layer is 20 nm.
[0082] (5) The CdSeS / CdZnS / CdSeS / ZnS composite material is dissolved in a solvent to form a quantum dot ink, which is then spin-coated onto the hole transport layer. After drying to form a film, it is annealed at an ambient temperature of 100°C for 10 minutes to form a quantum dot luminescent layer. The thickness of the quantum dot luminescent layer is 15 nm, and the band gap of the second shell of the composite material is the same as the band gap of the core.
[0083] (5) ZnO ink is spin-coated onto the quantum dot light-emitting layer, dried in a vacuum environment to form a film, and then annealed at an ambient temperature of 80°C for 15 minutes to form an electron transport layer, wherein the thickness of the electron transport layer is 30 nm.
[0084] (6) Ag is deposited onto the electron transport layer by vapor deposition to form a cathode layer, wherein the thickness of the cathode is 150 nm.
[0085] (7) An encapsulation is prepared on the cathode layer to obtain an optical device.
[0086] Example 2:
[0087] (1) Provide a glass substrate and place the glass substrate inside a nitrogen glove box.
[0088] (2) An ITO anode is prepared on the glass substrate.
[0089] (3) The water-soluble conductive polymer PEDOT:PSS is spin-coated onto the ITO anode, dried to form a film, and then annealed at an ambient temperature of 150°C for 15 min to form a hole injection layer, wherein the thickness of the hole injection layer is 45 nm.
[0090] (4) TFB ink is spin-coated onto the hole injection layer, dried to form a film, and then annealed at an ambient temperature of 230°C for 30 minutes to form a hole transport layer, wherein the thickness of the hole transport layer is 20 nm.
[0091] (5) The CdSeS / CdS / CdSe / ZnS composite material is dissolved in a solvent to form a quantum dot ink, which is then spin-coated onto the hole transport layer. After drying to form a film, it is annealed at an ambient temperature of 100°C for 10 minutes to form a quantum dot luminescent layer. The thickness of the quantum dot luminescent layer is 15 nm, and the band gap of the second shell layer of the composite material is smaller than the band gap of the core.
[0092] (5) ZnO ink is spin-coated onto the quantum dot light-emitting layer, dried in a vacuum environment to form a film, and then annealed at an ambient temperature of 80°C for 15 minutes to form an electron transport layer, wherein the thickness of the electron transport layer is 30 nm.
[0093] (6) Ag is deposited onto the electron transport layer by vapor deposition to form a cathode layer, wherein the thickness of the cathode is 150 nm.
[0094] (7) An encapsulation is prepared on the cathode layer to obtain an optical device.
[0095] Example 3:
[0096] (1) Provide a glass substrate and place the glass substrate inside a nitrogen glove box.
[0097] (2) An ITO anode is prepared on the glass substrate.
[0098] (3) The water-soluble conductive polymer PEDOT:PSS is spin-coated onto the ITO anode, dried to form a film, and then annealed at an ambient temperature of 150°C for 15 min to form a hole injection layer, wherein the thickness of the hole injection layer is 45 nm.
[0099] (4) TFB ink is spin-coated onto the hole injection layer, dried to form a film, and then annealed at an ambient temperature of 230°C for 30 minutes to form a hole transport layer, wherein the thickness of the hole transport layer is 20 nm.
[0100] (5) The CdSeS / CdZnS / CdS / ZnS composite material is dissolved in a solvent to form a quantum dot ink, which is then spin-coated onto the hole transport layer. After drying to form a film, it is annealed at an ambient temperature of 100°C for 10 minutes to form a quantum dot luminescent layer. The thickness of the quantum dot luminescent layer is 15 nm, and the band gap of the second shell layer of the composite material is larger than the band gap of the core.
[0101] (5) ZnO ink is spin-coated onto the quantum dot light-emitting layer, dried in a vacuum environment to form a film, and then annealed at an ambient temperature of 80°C for 15 minutes to form an electron transport layer, wherein the thickness of the electron transport layer is 30 nm.
[0102] Comparative Example 1:
[0103] (1) Provide a glass substrate and place the glass substrate inside a nitrogen glove box.
[0104] (2) An ITO anode is prepared on the glass substrate.
[0105] (3) The water-soluble conductive polymer PEDOT:PSS is spin-coated onto the ITO anode, dried to form a film, and then annealed at an ambient temperature of 150°C for 15 min to form a hole injection layer, wherein the thickness of the hole injection layer is 45 nm.
[0106] (4) TFB ink is spin-coated onto the hole injection layer, dried to form a film, and then annealed at an ambient temperature of 230°C for 30 minutes to form a hole transport layer, wherein the thickness of the hole transport layer is 20 nm.
[0107] (5) After dissolving the CdSe / CdS / ZnS composite material in a solvent to form a quantum dot ink, it is spin-coated onto the hole transport layer. After drying to form a film, it is annealed at an ambient temperature of 100°C for 10 minutes to form a quantum dot light-emitting layer, wherein the thickness of the quantum dot light-emitting layer is 15 nm.
[0108] (5) ZnO ink is spin-coated onto the quantum dot light-emitting layer, dried in a vacuum environment to form a film, and then annealed at an ambient temperature of 80°C for 15 minutes to form an electron transport layer, wherein the thickness of the electron transport layer is 30 nm.
[0109] Test Result Analysis:
[0110] The light-emitting devices prepared by the methods in Examples 1-3 and Comparative Example 1 were subjected to performance tests. Under the same brightness of 1000 nits, the external quantum efficiency (EQE) and current efficiency were calculated by measuring the brightness and current using an IVL optical measurement instrument. The external quantum efficiency is the proportion of excitons converted into photons in the light-emitting device. The lifetime (LT95) of the light-emitting device was measured using a lifetime aging device, and the fluorescence quantum yield (PLQY) was measured using a commercial emission quantum yield measurement instrument. The test results are shown in Table 1 below.
[0111]
[0112]
[0113] Table 1
[0114] As can be seen from Table 1 above, by comparing the experimental data of Examples 1-3 with Comparative Example 1, the external quantum efficiency and current efficiency of the light-emitting device with the added second shell quantum dot light-emitting layer are basically the same, and both are greater than the external quantum efficiency and current efficiency of the light-emitting device without the second shell quantum dot light-emitting layer.
[0115] By comparing the experimental data of Examples 1 to 3, when the core material of the composite material is the same, as the band gap of the second shell gradually increases, the external quantum efficiency, current efficiency and fluorescence quantum yield of the light-emitting device increase, and the lifetime of the light-emitting device is significantly improved.
[0116] In summary, the composite material provided in this application, by adding a second shell with a small band gap between the first shell and the third shell, can improve the carrier injection efficiency, optimize the charge balance within the light-emitting device, and thus improve the luminous efficiency and lifespan of the light-emitting device.
[0117] Obviously, the embodiments described above are only some embodiments of this application, not all embodiments. The accompanying drawings show preferred embodiments of this application, but do not limit the patent scope of this application. This application can be implemented in many different forms; rather, the purpose of providing these embodiments is to provide a more thorough and comprehensive understanding of the disclosure of this application. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing specific embodiments, or make equivalent substitutions for some of the technical features. Any equivalent structures made using the content of this application's specification and drawings, directly or indirectly applied to other related technical fields, are similarly within the scope of patent protection of this application.
Claims
1. A composite material, characterized in that: It comprises an inner core and a first shell layer, a second shell layer and a third shell layer sequentially covering the inner core outwards; The band gap width of the first shell layer is greater than the band gap width of the second shell layer, and the band gap width of the third shell layer is greater than the band gap width of the second shell layer.
2. The composite material according to claim 1, characterized in that The first shell layer comprises at least two layers, and the band gap of the first shell layer gradually increases along the radial direction from the inner core to the third shell layer; and / or, The third shell layer includes at least two layers, and the band gap of the third shell layer gradually increases along the radial direction from the inner core to the third shell layer.
3. The composite material according to claim 1, characterized in that The conduction band of the third shell is higher than the conduction band of the first shell, and the conduction band of the first shell is higher than the conduction band of the second shell; The valence band of the third shell layer is lower than the valence band of the first shell layer, and the valence band of the first shell layer is lower than the valence band of the second shell layer.
4. The composite material according to any one of claims 1 to 3, characterized in that: The band gap width of the first shell layer is 2 to 3 eV; and / or, The band gap width of the second shell layer is less than 2 eV; and / or, The band gap width of the third shell layer is greater than 3 eV; and / or, The band gap width of the core is 1.5 to 2 eV.
5. The composite material according to any one of claims 1 to 3, characterized in that: The material of the core is selected from at least one of II-VI compounds, III-V compounds, II-V compounds, III-VI compounds, IV-VI compounds, I-III-VI compounds, II-IV-VI compounds or IV simple substances, wherein the material of the core is selected from at least one of CdSe, CdS, ZnSe, ZnS, CdTe, CdZnS, CdZnSe, ZnSeS, ZnSeTe, ZnTeS, CdSeS, CdSeTe, CdTeS, CdZnSeS, CdZnSeTe, CdZnSTe, CdSeSTe, ZnSeSTe, CdZnSeSTe, InP, InAs, InAsP; and / or, The materials of the first shell layer, the second shell layer and the third shell layer are selected from at least one of CdS, ZnSe, ZnS, CdSeS and ZnSeS.
6. The composite material according to claim 4, characterized in that The composite material is at least one of CdSe@CdS@CdSe@ZnS, CdSe@CdSeS@CdSe@ZnS, CdSeS@CdS@CdSe@ZnS, CdSeS@CdZnS@CdS@ZnS, and CdSeS@CdZnS@CdSeS@ZnS.
7. The composite material according to claim 1, characterized in that The thickness of the core is 1 to 10 nm; and / or, The thickness of the first shell layer is 1 to 10 nm; and / or, The thickness of the second shell layer is 1 to 10 nm; and / or, The thickness of the third shell layer is 1-10 nm.
8. The composite material according to any one of claims 1 to 3, characterized in that: The composite material further includes an organic ligand, and the surface of the third shell layer is connected to the organic ligand.
9. The composite material according to claim 8, characterized in that The material of the organic ligand is selected from at least one of acid ligands, thiol ligands, amine ligands, (oxygen) phosphine ligands, phospholipids, phospholipids, polyvinyl pyridine, etc., wherein the acid ligand includes at least one of decadecanoic acid, undecylenic acid, tetradecanoic acid, oleic acid and stearic acid; the thiol ligand includes at least one of octadecyl mercaptan, dodecyl mercaptan and octadecyl mercaptan; the amine ligand includes one or more of oleylamine, octadecylamine and octaamine; the (oxygen) phosphine ligand includes at least one of trioctylphosphine and trioctylphosphine oxide.
10. A film, characterized in that: The material of the film comprises the composite material according to any one of claims 1 to 9.
11. A light emitting device, characterized in that: It includes an anode layer, a hole functional layer, a light emitting layer, an electron functional layer and a cathode layer stacked in sequence; Wherein, the light-emitting layer adopts the thin film as claimed in claim 10.
12. The light emitting device according to claim 11, characterized in that The material of the anode layer and / or the cathode layer includes one or more of metal, carbon material and metal oxide, the metal includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb and Mg; the carbon material includes one or more of graphite, carbon nanotubes, graphene and carbon fiber; the metal oxide includes doped or undoped metal oxide, including one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO, or includes a composite electrode with a metal sandwiched between doped or undoped transparent metal oxides, the composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2; and / or, The hole functional layer includes a hole injection layer and a hole transport layer, and the material of the hole injection layer and / or the hole transport layer includes at least one of TFB, CuPc, PVK, Poly-TPD, PFB, DNTPD, TCATA, TCCA, CBP, TPD, NPB, NPD, PEDOT:PSS, TAPC, MCC, F4-TCNQ, HATCN, 4,4',4'-tris(N-3-methylphenyl-Nphenylamino)triphenylamine, polyaniline, transition metal oxides, transition metal sulfides, transition metal tinides, doped graphene, undoped graphene and C60; and / or, The electronic functional layer includes an electron transport layer, and the material of the electron transport layer includes inorganic materials and / or organic materials. The inorganic material is selected from at least one of doped or undoped zinc oxide, barium oxide, aluminum oxide, nickel oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, nickel oxide, lithium titanium oxide, zinc aluminum oxide, zinc manganese oxide, zinc tin oxide, lithium zinc oxide, indium tin oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc tin, indium phosphide, gallium phosphide, copper indium sulfide, copper gallium sulfide, and barium titanate, and the doped element includes at least one of aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium; the organic material is selected from at least one of quinoxaline compounds, imidazole compounds, triazine compounds, fluorene compounds, and hydroxyquinoline compounds.